Resistance of Abaca Somaclonal Variant Against Fusarium - RULLY DYAH PURWATI; SUDARSONO SUDARSONO (Bogor Agricultural University, Indonesia, 2007)
The objectives of this study were (i) to evaluate responses against F. oxysporum f.sp. cubense (Foc) infection of abaca variants regenerated using four different methods, (ii) to determine initial root length and plant height effects on survival of inoculated abaca variants, and (iii) to identify Foc resistance abaca variants. In the previous experiment, four abaca variant lines were regenerated from (i) embryogenic calli (TC line), (ii) ethyl methyl sulphonate (EMS) treated embryogenic calli (EMS line), (iii) EMS treated embryogenic calli, followed by in vitro selection on Foc culture filtrate (EMS+CF line), and (iv) EMS treated embryogenic calli, followed by in vitro selection on fusaric acid (EMS+FA line). All abaca variants were grown in a glasshouse and inoculated with Banyuwangi isolate of Foc (Foc Bw). Initial root length (RL) and plant height (PH) of the abaca variants were recorded before inoculation, while scores of plant damage (SPD), and their survival were recorded at 60 days after inoculation (DAI). The results showed that the initial RL and PH did not affect survival of the tested abaca variants. Regardless of their initial RL and PH, susceptible abaca variants died before 60 DAI while resistance ones still survived. Abaca variants regenerated from single clump of embryogenic callus showed an array of responses against Foc Bw infection, indicating the existence of a mix cells population. The Foc Bw resistance abaca variants were successfully identified from four tested abaca variant lines, although with different frequencies. However, more Foc Bw resistance abaca plants were identified from EMS+CF line than the others. Using the developed procedures, 8 resistance abaca plants were identified from abaca cv. Tangongon and 12 from abaca cv. Sangihe-1. Key words: Fusarium wilts resistance, in vitro selection, culture filtrate, fusaric acid, EMS